THE IMPACT OF FOREIGN DIRECT INVESTMENT ON ECONOMIC GROWTH IN THE CONDITIONS OF SYSTEMIC CRISIS: EMPIRICAL EVIDENCE FROM UKRAINE - CHERKASHYNA, Tetiana (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is devoted to the determining of the quantitative impact of foreign direct investment (by industry affiliation) on economic growth in Ukraine in the conditions of systemic crisis (2019-2023) using multifactor correlation analysis in programming environment MS Excel. In the research as independent variables (or regressors) were chosen the following indicators: the size of foreign direct investment in machinery, the size of foreign direct investment in agriculture, fisheries and forestry, the size of foreign direct investment in the food industry, the size of foreign direct investment in construction, the size of foreign direct investment in metallurgy and metal production, the size of foreign direct investment in wholesale and retail trade and vehicle repair, the size of foreign direct investment in finance and insurance, the size of foreign direct investment in real estate transactions. As dependent variable (or regressand) was chosen the size of gross domestic product of Ukraine. The research consisted of five stages that are the following formation of the input data base (stage 1), selection of the most significant factors for multifactor correlation analysis (stage 2), evaluation of the input data required for multifactor correlation analysis (stage 3), modeling the relationship between input factors and the performance indicator (stage 4), economic interpretation of the results of multifactor correlation analysis (stage 5). As a result, it has been investigated that three factors had the greatest impact on economic growth in Ukraine in 2019-2023. These are size of foreign direct investment in agriculture, fisheries and forestry, size of foreign direct investment in construction and size of foreign direct investment in wholesale, retail trade and repair of motor vehicles. Increase in direct foreign investments in these sectors of Ukrainian economy will accelerate the modernization of production capacities, create new, more flexible management systems, and prepare all the necessary scientific and technological conditions for overcoming the systemic crisis and further structural changes.
Keywords: foreign direct investment (FDI); foreign capital stock; investment attractivity; economic growth; gross domestic product (GDP); multifactor correlation analysis; regression model